A Case Study: Nursing Care in Stroke Patients with Impaired Skin Integrity - Suwanto, Agus Wiwit; Endang Purwaningsih; Heru Wiratmoko; Marcella Linda Indriani (Poltekkes Kemenkes Malang, Campus III Blitar, 2025)
Stroke is one of the leading causes of long-term disability that often results in impaired skin integrity due to immobilization. This study aimed to analyze nursing care for stroke patients with impaired skin integrity at Dr. Harjono Regional Hospital, Ponorogo. A case study with a descriptive qualitative approach was conducted on a 66-year-old patient who experienced stroke and pressure ulcers. Data were collected through interviews, observation, physical examination, and risk assessment using the Braden Scale. Nursing interventions included pressure ulcer management, skin condition monitoring, adequate nutritional support, and repositioning every two hours to prevent further tissue damage. The results showed an improvement in the Braden Scale score from 11 (high risk) to 16 (low risk) after seven days of nursing care, indicating better skin condition and reduced tissue impairment. Evaluation revealed that impaired skin integrity problems were resolved following consistent implementation of nursing interventions. This study concludes that a holistic nursing approach, including nutritional support and family involvement, plays an essential role in preventing further complications and enhancing the quality of nursing care in stroke patients.